A review on the treatment and control of ectoparasite infestations in equids. Issue 5 (3rd June 2020) - Karasek, Inga; Butler, Catherine; Baynes, Ronald; Werners, Arno
Abstract : Ectoparasites infestations are a growing concern to horse owners and equine veterinarians alike. Ectoparasites cause significant health and welfare issues and can potentially can serve as vectors for a variety of pathogens. The prevalence of ectoparasites increases around the world, and especially in horses information on the successful prevention and treatment of ectoparasite infestations in scarce and in many instances anecdotal. This poses a challenge to the equine veterinarian and off‐label use of drugs can lead to detrimental effects in horses. In this review we describe the current available evidence for the prevention and treatment of ectoparasite infestations in horses. Only a very limited number of products is approved for the use in horses and fortunately many of the other products that are used in an off‐label manner appear to be safe in horses. Future research in this area should aim at providing PK/PD modelling data to assure appropriate and safe dose regimen to prevent and treat ectoparasite infestations in horses.